Role of plant cell in host-pathogen interactions: Lactuca spp.-Bremia lactucae - M. Sedlářová; A. Lebeda; P. Binarová; L. Luhová (Plant Protection Science, 2002)
Reactions of Lactuca spp. genotypes with different mechanisms of compatibility/incompatibility to B. lactucae race NL16 were examined. Microscopical study revealed significance of initial stages of infection for establishment of the host-pathogen relation. Incompatibility to the pathogen race is mostly expressed as hypersensitive reaction (HR). Rearrangement of cytoskeleton can participate in blocking of fungus penetration in resistant genotypes as well as support development of fungal infection structures in susceptible ones. During infection process peroxidase is activated, H2O2 released and phenolic compounds deposited. These defence processes well correspond with the expression of resistance. On the other hand, formation of callose attending pathogenesis is not directly related to incompatibility.